2022
DOI: 10.3389/fmicb.2022.860128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Torulaspora delbrueckii During Fermentation on Aromatic Profile of Vidal Blanc Icewine

Abstract: Non-Saccharomyces yeasts usually have a positive effect on improving the diversity of wine aroma and increasing the differentiation of wine products. Among these non-Saccharomyces yeast species, Torulaspora delbrueckii is often studied and used in winemaking in recent years, but its application in icewine has not been reported yet. In this study, indigenous T. delbrueckii strains (TD1 and TD2) and Saccharomyces cerevisiae strains (commercial yeast SC1 and indigenous icewine yeast SC2) were sequentially inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Many studies have shown that non- Saccharomyces yeasts (such as C. zemplinina ) have the effect of reducing ethanol content in wine fermentation (Giaramida et al, 2013 ; Contreras et al, 2014 ; Englezos et al, 2019 ). In recent years, consumers have become more interested in wines with lower ethanol concentrations for health and taste reasons (Ballester-Tomás et al, 2017 ; Li et al, 2022 ), and higher ethanol concentration has an undesired effect of reducing the complexity of wine sensory properties (Contreras et al, 2014 ). In terms of glycerol, higher glycerol content in the mixed culture fermented icewines suggested that C. railenensis could increase glycerol yield; therefore, the smoothness and viscosity of icewine structure/body perception of mixed culture fermentation should be stronger than those of the control fermentation (Swiegers et al, 2005 ), and the sensory analysis confirmed this fact.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that non- Saccharomyces yeasts (such as C. zemplinina ) have the effect of reducing ethanol content in wine fermentation (Giaramida et al, 2013 ; Contreras et al, 2014 ; Englezos et al, 2019 ). In recent years, consumers have become more interested in wines with lower ethanol concentrations for health and taste reasons (Ballester-Tomás et al, 2017 ; Li et al, 2022 ), and higher ethanol concentration has an undesired effect of reducing the complexity of wine sensory properties (Contreras et al, 2014 ). In terms of glycerol, higher glycerol content in the mixed culture fermented icewines suggested that C. railenensis could increase glycerol yield; therefore, the smoothness and viscosity of icewine structure/body perception of mixed culture fermentation should be stronger than those of the control fermentation (Swiegers et al, 2005 ), and the sensory analysis confirmed this fact.…”
Section: Discussionmentioning
confidence: 99%
“…This conversion can be catalyzed by enzymes during wine fermentation or in the presence of low pH values [39]. It provides a citrus and fresh orange aroma to the wine [40]. Lastly, among the miscellaneous compounds, the presence of 2,4-di-tert-butylphenol and 3,5-di-tert-butyl-4hidroxybenzaldehyde stands out, which were produced by S. cerevisiae and was present in all wines.…”
Section: Pattern Recognition Using the Semiquantitative Sbse-gc-ms Mi...mentioning
confidence: 99%